PERANCANGAN POROS DAN BEARING PADA MESIN PERAJANG SINGKONG - VINA N VAN HARLING; Herryanto Apasi (LPPM Politeknik Saint Paul Sorong, 2018)
Cassava chopper machine is a machine that serves to help or lighten human work in the process of chopping cassava. The working process of this cassava chopper machine uses an electric motor as a drive to rotate the cassava cutter blade shaft which is connected using a pulley and belt. The shaft is a very important component in a cassava chopper machine because it functions as a successor to the power and rotation of an engine component to other machine elements. Considering that shaft functions are very important, these components must be designed and ensured to be able to work well when receiving loading and have a service life as expected. Based on the power plan data based on the calculation results obtained 0.55kW, the results of the calculation of the moment of the plan amounted to 1847 Kg.mm. Based on the calculation of the value of the shear stress obtained by 6.66 kg / mm2 while the measurement of the shaft diameter is 14.7 mm. The results of measuring the diameter of the shaft are close to the size of the shaft diameter used when making cassava chopper machines that are equal to 15 mm. After the calculation results of the shaft have been determined then to determine the bearing that will be used on the cassava chopper machine is a rolling bearing with UPC 202 type with a diameter of 15mm.